ANALISIS FAKTOR YANG MEMPENGARUHI KEPUASAN MAHASISWA TERHADAP PELAYANAN PADA STIMI BANJARMASIN - Mahfuzil Anwar; Abdul Wahab (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
Abstract, This study aims to examine the variable Direct Evidence (Tangibles), Reliability (Reliability), Responsiveness (Responsiveness), Assurance (Assurance), and Empathy (Empaty), simultaneously affect the satisfaction of STIMI Banjarmasin students and test which factors are more dominant influence on satisfaction STIMI Banjarmasin students. Population of 572 students enrolled in the 2020 Porlap Dikti, Simple Random Sampling was taken as many as 100 STIMI Banjarmasin students. The statistical method used is multiple regression. The results showed that the regression results through the F test, Tangibles, Reliability, Responsiveness, Assurance, and Empathy variables simultaneously / jointly affected the satisfaction of STIMI Banjamasin students. This is evidenced by looking at F count greater than F table (Fcount 6.784> F table 2.311) or p <0.05, so that Hypothesis I states that the factor (X1) Direct Evidence (Tangibles), Reliability (Reliability), (X2) Responsiveness, (X3) Assurance (X4) and Empathy (Empaty), (X5) simultaneously have a significant effect on Student Satisfaction (Y) declared acceptable. The results of regression through t test (partially), as proof of Hypothesis II That among the factors studied, factor (X2) Responsiveness has a more dominant influence on student satisfaction (Y). From the regression results through the t test (partially), obtained tcount Direct Evidence (Tangibles) (X1) = 3,538, Reliability (X2) = 1,181, tcount (X3) Responsiveness = 0.855, tcount (X4) Guarantee (Assurance) = 2.455, and tcount (X5) Empathy (Empaty), = 2.597. From the results above it turns out that the variable (X1) Direct evidence (Tangibles) is the dominant variable affecting student satisfaction, therefore Hypothesis II is declared rejected.